1994
DOI: 10.1002/pts.2770070305
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of polymer homologues and additives with SFE/SFC‐MS coupling

Abstract: A rapid and easy analysis method for polymers is presented. The method involves sample preparation by SFE, separation of the extracted compounds by SFC and simultaneous quantitative detection by FID, as well as identification of unknowns by MS. The applications illustrate how structural research work and routine polymer analysis can be done with this time saving method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…This coupled approach, SFE-SFC, often combined with MS, found great utility in the evaluation of polymer homologs and additives. One group demonstrated the approach for both structural research work and routine polymer analysis (246). Meanwhile, McKay and Smith developed SFE-SFC/MS for the study of organophosphate flame retardants in polyurethane foams (239) and other polyurethane additives (240).…”
Section: Sfe Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This coupled approach, SFE-SFC, often combined with MS, found great utility in the evaluation of polymer homologs and additives. One group demonstrated the approach for both structural research work and routine polymer analysis (246). Meanwhile, McKay and Smith developed SFE-SFC/MS for the study of organophosphate flame retardants in polyurethane foams (239) and other polyurethane additives (240).…”
Section: Sfe Applicationsmentioning
confidence: 99%
“…Other publications described the use of SFC to study species that could potentially migrate from packaging polymers. Additives in packaging polymers were separated by Buecherl et al using SFC with FID and MS detection ( , ). They used on-line SFE to extract the additives from the polymers and found the combined methods offered considerable time savings.…”
Section: (Achiral) Sfc Applicationsmentioning
confidence: 99%
“…14 In addition, on-line SFE-cSFC-MS studies on polymer additives have been reported. 15,16 All of these applications have used capillary columns, which are capable of providing high resolution, with analysis times between 40 and 60 min. However, most polymers contain relatively few additives, and therefore the high resolving power of capillary columns is not required, and separations have been achieved in less than 10 min using pSFC.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of SFE and SFC has been reported in many fields such as pharmaceutical analysis, material science, and biological sample analysis. Online SFE‐SFC has united the extraction and analysis process; SFE module could greatly simplify the complicated pretreatment procedure into just crushing and stuffing samples to the extraction tank; thereafter, the extract is directly led to SFC part, realizing the sequential extraction and analysis.…”
Section: Introductionmentioning
confidence: 99%